Land Management on First Nations Reserves: Lawful Possession and Its Determinants - Brinkhurst, Marena; Kessler, Anke S. (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2013)
Much debate concerning property rights on reserves in Canada focuses on socio-economic impacts and the potential for individualized land tenure to support economic development, thereby reducing poverty. Study of existing forms of individual property on reserves is needed to inform these debates. In this article, we examine data on the lawful possession (Certificate of Possession) system that is currently used on reserves across Canada. We provide descriptive statistics regarding the variability of lawful possessions across First Nations and using regression analysis we assess which socio-economic, demographic, and locational variables influence the use of lawful possessions instead of communal land or other customary land holding systems. We show that use of the lawful possession system is surprisingly low and very uneven. As well, our regression results suggests that using the system requires a relatively educated community with low levels of poverty, with a favourable geographic location. Overall, the results are consistent with the view that lawful possessions are not primarily used to foster economic development.